Modelling of the strategic planning process at an agricultural enterprise - Iryna Boryshkevych; Aleksander Iwaszczuk (Vasyl Stefanyk Precarpathian National University, 2020)
The development strategy is a long-term roadmap of the company's activities, which makes it possible to achieve higher performance in relation to competitors. Almost all managers of agricultural enterprises in the process of strategic management face a number of problems, such as the choice of appropriate tools for strategic analysis and methods for building a strategy. This is based on the fact that different agricultural enterprises have different existing capabilities, available resources and strategic planning needs. Depending on the strategic ability of agricultural enterprises, it is proposed to use various tools of strategic analysis and methods of strategy development. Based on the conducted research, there was formed a mechanism for implementing strategic planning at an agricultural enterprise. It consists of three stages. The developed mechanism was tested at a private agricultural enterprise 'Ridna Zemlia' (Native Land) with the typical main indicators of economic activity in the Ivano-Frankivsk region. At the first stage, using a balanced system of economic indicators, it was found that this enterprise has an average level of strategic ability. Following the recommended strategic analysis tools, at the second stage of strategic planning, SWOT analysis of an agricultural enterprise was conducted identifying its strengths and weaknesses, existing opportunities and threats. At the third stage, a roadmap for implementing the strategy was developed within the framework of using the road mapping method, which is allowed by the appropriate level of strategic capability. The main strategic goal of the developed strategy is to ensure sustainable profits in the long term by increasing the productivity and efficiency of agricultural production. Based on this, the following strategic tasks were proposed to implement: the introduction of a new technology, which consists of constant monitoring of the herd of cows, opening of a new farm to expand the existing market and increase production volumes, the construction of a pellet boiler farm using biofuels, as well as the formation of a personnel training plan and the development and implementation of training programs for employee development.